Pemanfaatan Limbah Abu Terbang Sebagai Penguat Aluminium Matrix Composite - Subarmono Subarmono; Jamasri Jamasri; M.W. Wildan; Kusnanto Kusnanto (Institute of Research and Community Outreach, Petra Christian University, 2008)
This research aims to utilize fly ash which is obtained from waste of combustion of coal in steam power plant as a reinforcement of aluminum matrix composite (AMC). The amounts of fly ash of 2.5%, 5%, 7.5% and 10% wt were added to fine aluminum powder (dimension of particles are smaller than 40 µm). Each composition was mixed using a rotary mixer for 3 hr. The mixture was uniaxially pressed and it was followed by isostatic compaction with a pressure of 100 MPa to produce green bodies. They was pressureless sintered in argon atmosphere at various temperatures of 500°C, 525°C, 550°C, 575°C and 600ºC. Bending strength, Vickers hardness, wear resistance, density of the AMC were tested, and the microstructures were observed using SEM. The results show that the mechanical properties increase with increasing the fly ash content up to 5% wt. The bending strength, hardness, porosity and wear rate are 74 MPa, 66 VHN, 4.5% and 0.04 mg/(MPa.m), respectively. Abstract in Bahasa Indonesia: Penelitian ini bertujuan untuk memanfaatkan abu terbang sebagai penguat komposit bermatrik aluminium (AMC). Abu terbang merupakan limbah pembakaran batu bara pada pembangkit listrik tenaga uap. Abu terbang sejumlah 2,5%; 5%; 7,5% dan 10% berat dicampur dengan serbuk aluminium (ukuran serbuk lebih kesil dari 40 µm). Setiap campuran diaduk menggunakan rotay mixer selama 3 jam. Campuran aluminum dan abu terbang dikompaksi secara uniaksial dilanjutkan kompaksi secara isostatik dengan tekanan 100 MPa dan diikuti sintering tanpa tekanan dengan lingkungan gas argon dan variasi temperatur 500°C, 525°C, 550°C, 575°C dan 600°C. Kekuatan bending, kekerasan Vickers, ketahanan aus dan densitas komposit diuji serta struktur mikro diamati menggunakan SEM. Hasil pengujian menunjukkan bahwa sifat mekanis meningkat seiring dengan peningkatan fraksi berat abu terbang sampai 5% berat, selebihnya terjadi penurunan. Kekuatam bending, kekerasan Vickers, porositas dan laju keausan berturut-turut 74 MPa, 66 VHN, 4,5% dan 0,04 mg/(MPa.m). Kata kunci: Aluminum Matrix Composite, abu terbang, kompaksi, isostatik.